A novel mechanism of the M1‐M2 methionine adenosyltransferase switch‐mediated hepatocellular carcinoma metastasis. Issue 9 (27th May 2018) - Wang, Ruizhi; Jin, Yi; Yao, Xue‐Hua; Fan, Wenzhe; Zhang, Jiang; Cao, Yihai; Li, Jiaping
Abstract : Hepatocellular carcinoma (HCC) manifests as a highly metastatic cancer with extremely poor prognosis. However, mechanisms underlying metastasis of HCC are not fully understood. Here, we showed that switching gene expression from MAT1A to MAT2A (M1‐M2 switch) promoted cancer invasion and metastasis. Reversion of the M1‐M2 switch repressed, whereas enhancing the M1‐M2 switch promoted the ability of HCC cells to metastasize. Moreover, we provided clinical data showing that tipping the balance between MAT1A and MAT2A expression correlated with increased metastasis and inferior recurrence‐free survival in HCC patients. Molecular pathways analysis showed that downregulation of MAT1A, which augmented osteopontin (OPN) expression through decreasing methylation of the OPN promoter, and MAT2A upregulation, which induced integrin β3 (ITGB3) expression by binding to ITGB3 promoter, collaboratively triggered ERK signaling and thereby promoted metastasis. Thus, the simultaneous downregulation of MAT1A and upregulation of MAT2A are necessary and sufficient for HCC metastasis in the process of M1‐M2 switch. Our findings provide novel mechanistic insights into cancer metastasis. Inhibition and prevention of the M1‐M2 switch would offer a novel therapeutic option for treatment of HCC.